Peculiarities of metallization of polyvinyl chloride granules - Кучеренко, А.; Нікітчук, О.; Кузнецова, М.; Моравський, В.; Kucherenko, A.; Nikitchuk, O.; Kuznetsova, M.; Moravskyi, V. (Lviv Politechnic Publishing House, 2020)
Наведено результати експериментальних досліджень міднення гранул полівінілхлориду в розчині хімічного осадження. Досліджено вплив площі поверхні гранул полівінілхлориду на кінетичні закономірності відновлення міді і вміст міді на металізованих гранулах. Встановлено, що площа поверхні гранул полівінілхлориду має значний вплив на швидкість відновлення іонів міді і ніяк не впливає на кількість відновленої міді. Розраховано товщину шару одержаної мідної оболонки на гранулах полівінілхлориду різного розміру залежно від вмісту металу.

The results of experimental studies of copper plating of polyvinyl chloride granules in a chemical precipitation solution are presented. The influence of the surface area of polyvinyl chloride granules on the kinetic regularities of copper reduction and the copper content on metallized granules has been studied. It is established that the surface area of polyvinyl chloride granules has a significant effect on the rate of reduction of copper ions and does not affect the amount of reduced copper. The thickness of the layer of the obtained copper shell on polyvinyl chloride granules of different sizes depending on the metal content is calculated.
Особливості металізації гранул полівінілхлориду
Keywords: полівінілхлорид; гранули; хімічна металізація; мідь; оболонка; polyvinyl chloride; granules; chemical metallization; copper; shell